Pressure Sensors: Ultrasensitive Pressure Detection of Few‐Layer MoS2 (Adv. Mater. 4/2017). Issue 4 (January 2017) - Yu, Feifan; Liu, Qianwen; Gan, Xin; Hu, Mingxiang; Zhang, Tianyi; Li, Cheng; Kang, Feiyu; Terrones, Mauricio; Lv, Ruitao
Abstract : In article 1603266, C. Li, M. Terrones, R. Lv and co‐workers propose an ultrasensitive fiber‐optic Fabry–Perot acoustic pressure sensor using 2D MoS2 films. The device has inherent immunity to electromagnetic interference and exhibits nearly synchronous pressure‐deflection responses with a record high sensitivity of 89.3 nm Pa −1 . This breakthrough may open up new avenues for 2D materials in sensor and communication applications.